Opium for the masses?: conflict-induced narcotics production in Afghanistan - Jo Thori Lind; Karl Ove Moene; Fredrik Willumsen (Center for Economic Studies and ifo Institute (CESifo), 2009)
We show that the recent rise in Afghan opium production is caused by violent conflicts. Violence destroys roads and irrigation, crucial to alternative crops, and weakens local incentives to rebuild infrastructure and enforce law and order. Exploiting a unique data set, we show that Western hostile casualties, our proxy for conflict, have strong impact on subsequent local opium production. This proxy is shown to be exogenous to opium. We exploit the discontinuity at the end of the planting season: Conflicts have strong effects before and no effect after planting, assuring causality. Effects are strongest where government law enforcement is weak.
Keywords: D74; H56; K42; O1; 330; Conflict; narcotics production; resource curse; Afghanistan; Drogenwirtschaft; Pflanzenbauprodukt; Politischer Konflikt; Rechtsdurchsetzung; Afghanistan